Electrical Stimulation Promotes Stem Cell Neural Differentiation in Tissue Engineering - Hong Cheng; Yan Huang; Hangqi Yue; Yubo Fan (Hindawi Limited, 2021)
Nerve injuries and neurodegenerative disorders remain serious challenges, owing to the poor treatment outcomes of in situ neural stem cell regeneration. The most promising treatment for such injuries and disorders is stem cell-based therapies, but there remain obstacles in controlling the differentiation of stem cells into fully functional neuronal cells. Various biochemical and physical approaches have been explored to improve stem cell-based neural tissue engineering, among which electrical stimulation has been validated as a promising one both in vitro and in vivo. Here, we summarize the most basic waveforms of electrical stimulation and the conductive materials used for the fabrication of electroactive substrates or scaffolds in neural tissue engineering. Various intensities and patterns of electrical current result in different biological effects, such as enhancing the proliferation, migration, and differentiation of stem cells into neural cells. Moreover, conductive materials can be used in delivering electrical stimulation to manipulate the migration and differentiation of stem cells and the outgrowth of neurites on two- and three-dimensional scaffolds. Finally, we also discuss the possible mechanisms in enhancing stem cell neural differentiation using electrical stimulation. We believe that stem cell-based therapies using biocompatible conductive scaffolds under electrical stimulation and biochemical induction are promising for neural regeneration.